Hydrocarbon Potential Evaluation of Sandstone Reservoirs in Lower Goru Formation Miano Gas Field in Middle Indus Basin, Sindh, Pakistan - Saeed Ahmed; Sadaf Naseem (International Journal of Economic and Environment Geology)
The Middle Indus basin (MIB) is a potential hydrocarbon sedimentary basin of Pakistan. This study was carried out to interpret the petrophysical well log data of Minao gas field of three wells (Miano-1, 2 and 3) to characterize the Lower Goru reservoir. Indonesian model was applied to estimate the in - situ water saturation Sw of the Lower Goru reservoir. Contour maps were used to understand the lateral and vertical variation in reservoir characteristics. In addition, M-N lithology cross plots were also used to interpret the lithological heterogeneity and homogeneity within the reservoir. There were four sand units recognized as Sand A, B, C and D within Lower Goru reservoir based on the estimation of effective porosity (Фeff), permeability (K), shale volume (Vsh), water saturation (Sw) and hydrocarbon saturation (Shc). The Sand B showed good potential for hydrocarbon as indicated by shale volume Vsh (10 to 14%), effective porosity Фeff (19 to 22%), permeability K (798 to 847 mD), water saturation Sw (19 to 22%) and hydrocarbon saturation Shc (77 to 80%). Data revealed that in north and northeast side, there is an increase in reservoir quality and thickness, while it decreased in south to southwest side. Shale volume decreased in north to northeast with low water saturation and high hydrocarbon saturation. Results reveal that north to northeast direction of Miano gas field is ideal for the hydrocarbon recovery. More exploratory wells are recommended to be drilled in this direction to maximize the hydrocarbon production from the Lower Goru reservoir.